P4-S3.08 Development of a novel chimeric protein construct for improved diagnosis of syphilis. (10th July 2011) - Smith, B; Cameron, C
Abstract : Objectives: To develop a novel diagnostic protein in order to enhance early detection of syphilis infections and improve overall syphilis diagnosis. Methods: Using pooled serum samples from patients infected with syphilis, immunoreactive regions of two previously identified diagnostic protein candidates, Tp0326 and Tp0453, were elucidated. Focusing on these regions, a chimeric protein construct was created for expression in Escherichia coli and expression conditions were optimised to produce soluble protein expression. This Tp0326/Tp0453 chimeric construct was screened against serum samples from; patients with primary, secondary, latent, and neurosyphilis and uninfected individuals. These results were directly compared to the rapid plasma regain (RPR) test, and the microhemagglutination assay for T pallidum (MHA-TP). Results: Screening results show high degrees of sensitivity and specificity for the Tp0326/Tp0453 chimeric construct, identifying all stages of syphilis infection from early primary to late latent. Conclusion: The Tp0326/Tp0453 chimera shows promise as a new diagnostic antigen for detecting all stages of syphilis infection and for development into point-of-care diagnostic test formats.